Commerzbank Headquarters, Frankfurt - Norman Foster (Oz, 1996)
The new headquarters for Commerzbank in Frankfurt is the world's first ecological high-rise tower. The outcome of a limited international competition held in 1991, our design transforms the fundamental nature of a large office building by developing new ideas for the ecology and working patterns in an office environment.